ANALISIS MANAJEMEN RESIKO DI RUANG FILING RUMAH SAKIT UMUM DAERAH ADE MOHAMMAD DJOEN KABUPATEN SINTANG TAHUN 2023 - Herman, Joni (NHM PRESS, 2024)
Risk management is a logical and systematic method for identifying, quantifying, determining attitudes, determining solutions, and monitoring and reporting risks that occur in each activity or process. Officers may experience coughing and sneezing if they take or return medical record documents without wearing a mask due to the influence of dust and dirt. Objective: to find out risk management analysis in the filing room. Method: This type of qualitative research uses a descriptive approach. The research subjects were officers in the filing room and registration officers. Meanwhile, the research object is risk factors in the filing room. Results: Causes of damage to medical record documents are food, drink, fleas, termites, damp rooms and medical record documents should not be borrowed carelessly. In the filing room there are no stairs for medical records officers going in and out of the room without washing their hands first Conclusion: it is hoped that the hospital will know the factors that cause damage to medical record documents